1986
DOI: 10.1056/nejm198609253151304
|View full text |Cite
|
Sign up to set email alerts
|

Release of Prostaglandin D2into Human Airways during Acute Antigen Challenge

Abstract: Among the many possible mediators of the early asthmatic response, prostaglandin D2, a bronchoconstrictor, is the principal cyclooxygenase metabolite of arachidonic acid that is released upon the activation of mast cells and is also synthesized by human alveolar macrophages. We performed bronchoalveolar lavage in five patients with chronic stable asthma, before and up to nine minutes after local provocative challenge with Dermatophagoides pteronyssinus. The lavage fluid was analyzed for products of arachidonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
246
1
5

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(257 citation statements)
references
References 38 publications
5
246
1
5
Order By: Relevance
“…However, depending on the stimulus and according to the PGE 2 receptors recruited, the effects of PGE 2 on the immunostimulatory functions of differentiated DC are diverse and sometimes opposite [31]. PGD 2 represents another major cyclooxygenase metabolite produced in vivo during inflammation, particularly during allergic reactions [32]. Along with its dual role in the genesis and in the control of inflammatory reactions, PGD 2 is thought to be an important component of the immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, depending on the stimulus and according to the PGE 2 receptors recruited, the effects of PGE 2 on the immunostimulatory functions of differentiated DC are diverse and sometimes opposite [31]. PGD 2 represents another major cyclooxygenase metabolite produced in vivo during inflammation, particularly during allergic reactions [32]. Along with its dual role in the genesis and in the control of inflammatory reactions, PGD 2 is thought to be an important component of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Since micromolar concentrations of PGD 2 are detected in certain noninflamed tissues [42] such as the spleen and the bone marrow, it may be the case that PGD 2 modulates DC functions under steady-state conditions. Moreover, the enhanced production of PGD 2 in peripheral sites during inflammation, particularly during the allergic reaction [32] or tumor formation [43], highlights its role on DC functions in pathological conditions and suggests that PGD 2 may be an important component in the control of the immune response in these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of metabolites of thromboxane A2 (TXA2) have been measured in the plasma and urine following antigen provocation in asthmatics (Green et al, 1974;Shepherd et al, 1985;Sladek et al, 1990) and increased prostaglandin D2 (PGD2) and TXA2 levels have been observed in bronchoalveolar lung fluid obtained following antigen challenge (Murray et al, 1986;Wenzel et al, 1989;Liu et al, 1990). …”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, 15-deoxy-⌬ 12,14 -PGJ 2 (15d-PGJ 2 ) and ⌬ 12 -PGJ 2 are generated from PGJ 2 by albuminindependent and -dependent reactions, respectively (7). PGD 2 is emerging as one of the predominant factors released in large amounts by mast cells during asthmatic attacks in humans (8). PGD 2 binds to and activates two G-protein-coupled receptors, DP1 and CRTH2 (chemoattractant receptor-homologous molecule expressed on Th type 2 cells), also known as DP2.…”
mentioning
confidence: 99%